Framework for cost-effectiveness analysis of aflatoxin reduction - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
We tested the impact of subsidies for technologies that improve food safety and price premiums for safer produce in Kenya. Subsidization of aflatoxin control technologies is a cost-effective strategy for reducing liver cancer and possibly also for reducing stunting in children.